(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: This study examines Turkey’s position within the emerging regional balance of power following the fall of the Assad regime in December 2024. This represents a major strategic shift that has reshaped power and influence in the Arab Mashreq and shifted regional competition from regime survival to new state-building in Syria. Objective: The study analyzes the implications of Syrian transformations for Turkey’s national security and examines its role in security, economic reconstruction, and regional and international relations, while also exploring possible future trajectories of Turkey’s position in the evolving regional order. Methodology: The study adopts an analytical approach to examine regional dynamics associated with Syria’s transition and employs scenario-based foresight analysis to explore future trajectories of Turkey’s role. Results: The findings suggest that Turkey is among the main beneficiaries of post-Assad developments, and that its influence in Syria will depend on the success of state-building efforts. The Kurdish issue, border security, reconstruction processes, and trade corridors are identified as key determinants of Turkey’s role in the coming period. Conclusion: The study concludes that the fall of the Assad regime has contributed to reshaping the regional balance of power in the Arab Mashreq, positioning Turkey as a central actor in the emerging order. However, the sustainability of this role remains contingent on domestic stability in Syria and the evolving dynamics of regional and international interactions during the transitional phase.